Improving the Quality of Oocytes with the Help of Nucleolotransfer Therapy - Benc, Michal; Strejcek, Frantisek; Morovic, Martin; Bartkova, Alexandra; Murin, Matej; Gad, Ahmed; Bonnet-Garnier, Amelie; Percinic, Florina Popovska; Laurincik, Jozef (Pharmaceuticals (Basel, Switzerland), 2021)
The nucleolus is an important nucleus sub-organelle found in almost all eukaryotic cells. On the one hand, it is known as a differentiated active site of ribosome biogenesis in somatic cells, but on the other hand, in fully grown oocytes, zygotes, and early embryos (up to the major embryonic genome activation), it is in the form of a particular homogenous and compact structure called a fibrillar sphere. Nowadays, thanks to recent studies, we know many important functions of this, no doubt, interesting membraneless nucleus sub-organelle involved in oocyte maturation, embryonic genome activation, rRNA synthesis, etc. However, many questions are still unexplained and remain a mystery. Our aim is to create a comprehensive overview of the recent knowledge on the fibrillar sphere and envision how this knowledge could be utilized in further research in the field of biotechnology and nucleolotransfer therapy.
Keywords: embryo; nucleolus; nucleolotransfer; zygote; oocyte